PENGARUH ARUS KAS, LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP KEBIJAKAN DEVIDEN PADA BANK UMUM SYARIAH INDONESIA TAHUN 2017-2021 - Indah elfitriyanti (EKSYA : Jurnal Ekonomi Syariah, 2023)
The financial performance of a sharia bank is a description of the financial condition of a sharia bank in a certain period, either monthly, quarterly or annually which includes the collection and distribution of the sharia bank's funds. The purpose of this study is to analyze the effect of cash flow, the effect of liquidity, the effect of profitability, and the effect of leverage on dividend policy on the financial statements of Indonesian Islamic Commercial Banks for 2017-2021 and the distribution of Islamic bank funds. The type of research used is quantitative with a descriptive approach. The results of the study show that 1) The cash flow ratio has no effect on dividend policy on the financial statements of Indonesian Islamic Commercial Banks for 2017-2021. 2) The liquidity ratio has no effect on dividend policy in the financial statements of Indonesian Islamic Commercial Banks for 2017-2021. 3) Profitability ratios have an effect on dividend policy in the financial statements of Indonesian Islamic Commercial Banks for 2017-2021. 4) Leverage ratio has no effect on dividend policy in the financial statements of Indonesian Islamic Commercial Banks for 2017-2021. 5) The ratio of cash flow, liquidity, profitability and leverage together affect the dividend policy on the financial statements of Indonesian Islamic Commercial Banks for 2017-2021